Technical issues related to strengthening the peanut industry in Metro Manila area - Geronimo, Lorelie C.; Galvez, Flor Crisanta V. (1998.)
A study on peanut production, trade, utilization and a survey on technical constraints in the peanut industry in Metro Manila area were conducted. The purpose of the study is to identify the problems encountered by manufacturers in terms of raw material, processing, marketing and storage of peanut products and to relate this to peanut production, trade and utilization. The findings of the study revealed that peanut production in the country is very insufficient to supply the domestic demand. It slid by an average of 2.5% each year from 37,590 metric tons (MT) in 1989 to 34,028 MT in 1993. The insufficient production of peanut resuted to huge importation of this cash crop from other countries particularly China and USA leading to a large trade deficit of P 994 million in 1996. Utilization of peanuts has been increasing for the last twenty years. Results of the survey showed that high price (77.77%) and small size (72.22%) of local peanuts were the major problems of the industry on their raw material. In terms of products, 50% suffer problems on quality, shelf-life and randicity. In terms of operation problems, relatively high percentage (55.56%) suffers lack of appropriate equipment while 50% have problems on cost reduction. Shelf life is the major problem of the processors in marketing and storage. The study also revealed that majority (50%) still use traditional and conventional source of technology such as family tradition or trial and error and local practices except for local R&D institutes. The peanut industry relies on government support in addressing their problems particularly that on raw material supply.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Peanut industry -- Philippines -- Metro Manila